IPPI'S Communication Strategy in Engaging with the Community to Overcome Stigma Against Women with Hiv - Defita Dwinusa Cindana; Ani Berta; Tandio Saputro, Shania Safera (Jurnal Spektrum Komunikasi, 2025)
Stigma against women living with HIV in Indonesia remains a significant barrier to achieving quality of life, as it intersects with gender discrimination and societal exclusion. This study analyzes the communication strategies employed by the Indonesian Positive Women’s Network (IPPI) to counter stigma and reshape public perception. Using a descriptive qualitative method, data were collected through in-depth interviews with IPPI leaders and analyzed thematically using the Two-Step Flow of Communication Theory, empowerment communication, and intersectional feminist frameworks. The findings reveal that IPPI utilizes a multi-level approach involving social media, community opinion leaders, and culturally contextualized messaging to promote empathy, visibility, and trust. Empowerment narratives, digital storytelling, and grassroots collaborations were key strategies that shifted HIV discourses from victimization to agency. Despite challenges such as limited digital access, stigma-related fear, and inconsistent policy implementation, IPPI's bottom-up communication model fosters self-empowerment and social reintegration. This study contributes theoretically by expanding the application of the Two-Step Flow model in grassroots feminist communication and highlighting the role of lived experience in shaping public health narratives. Practically, it offers insights for civil society organizations on designing inclusive, emotionally resonant, and community-based communication strategies to combat health-related stigma. IPPI's case demonstrates how community-rooted communication can be a transformative force in both public perception and policy influence